Reinvestigating the Photoprotection Properties of a Mycosporine Amino Acid Motif - Whittock, Abigail L.; Turner, Matthew A. P.; Coxon, Daniel J. L.; Woolley, Jack M.; Horbury, Michael D.; Stavros, Vasilios G. (Frontiers in Chemistry, 2020)
With the growing concern regarding commercially available ultraviolet (UV) filters damaging the environment, there is an urgent need to discover new UV filters. A family of molecules called mycosporines and mycosporine-like amino acids (referred to as MAAs collectively) are synthesized by cyanobacteria, fungi and algae and act as the natural UV filters for these organisms. Mycosporines are formed of a cyclohexenone core structure while mycosporine-like amino acids are formed of a cyclohexenimine core structure. To better understand the photoprotection properties of MAAs, we implement a bottom-up approach by first studying a simple analog of an MAA, 3-aminocyclohex-2-en-1-one (ACyO). Previous experimental studies on ACyO using transient electronic absorption spectroscopy (TEAS) suggest that upon photoexcitation, ACyO becomes trapped in the minimum of an S1 state, which persists for extended time delays (>2.5 ns). However, these studies were unable to establish the extent of electronic ground state recovery of ACyO within 2.5 ns due to experimental constraints. In the present studies, we have implemented transient vibrational absorption spectroscopy (as well as complementary TEAS) with Fourier transform infrared spectroscopy and density functional theory to establish the extent of electronic ground state recovery of ACyO within this time window. We show that by 1.8 ns, there is >75% electronic ground state recovery of ACyO, with the remaining percentage likely persisting in the electronic excited state. Long-term irradiation studies on ACyO have shown that a small percentage degrades after 2 h of irradiation, plausibly due to some of the aforementioned trapped ACyO going on to form a photoproduct. Collectively, these studies imply that a base building block of MAAs already displays characteristics of an effective UV filter.